The Professions in Modernity and the Society of the Future: A Theoretical Approach to Understanding the Polyvalent Logics of Professional Work - Werner Vogd (Professions and Professionalism, 2017)
In this article, I draw attention to the societal arrangements that permit or produce the autonomy of professions since professionals have the task of holding the tension among different perspectives. To do so, they must apply differing, irreconcilable logics of reflection and balance them in their decision-making. To gain a differentiated understanding of the complexities of these processes, I propose a metatheoretical conceptualization of the dynamics of professions based on Gotthard Günther’s theory of “polycontexturality,” which can be used both to analyse the interaction processes and to embed them in society. I illustrate this argument with an example from the field of medical treatment. The proposed approach also lays the basis for a differentiated understanding of phenomena, which psychoanalysis has traditionally described in terms of transference and countertransference.